1980
DOI: 10.1002/jcp.1041050316
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester tumor promoters block the transition from the early to the heme‐dependent late program of friend cell differentiation

Abstract: In this study, the mechanism of inhibition of differentiation of Friend erythroleukemia cells by the phorbol ester tumor promoter, 12-O-tetradecanoylphorbol-13-acetate (TPA), has been examined. These studies indicate that some early events associated with Friend cell differentiation, including an early change in 86Rb+ transport and a decrease in cell volume, still occur in the presence of TPA. However, several late events in the program of Friend cell differentiation, including the induction of heme synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…A comparison of the spontaneous differentiation and self-renewal probabilities of CFU-FV-A and CFU-FV-P suggested that there is an inverse relationship between the proliferative and developmental capacities of these CFU-FV. This conclusion is consistent with findings on the relationship between the colony-forming ability and the extent of differentiation of permanent erythroid cell lines transformed by Friend virus (30).…”
Section: Discussionsupporting
confidence: 92%
“…A comparison of the spontaneous differentiation and self-renewal probabilities of CFU-FV-A and CFU-FV-P suggested that there is an inverse relationship between the proliferative and developmental capacities of these CFU-FV. This conclusion is consistent with findings on the relationship between the colony-forming ability and the extent of differentiation of permanent erythroid cell lines transformed by Friend virus (30).…”
Section: Discussionsupporting
confidence: 92%
“…Since differentiation-related, in contrast to inducer-related, slowing of cell proliferation occurred only after the cells accumulated haemoglobin, it might be argued that the accumulation of the maturation-specific products is responsible for the loss of the multiplication potential. This conclusion is backed by studies indicating the essential role for haem synthesis in the commitment to terminal cell division (Mager et al, 1979(Mager et al, , 1980. However, other studies have indicated that terminal cell division and the co-ordinated expression of the inducer-mediated differentiation products are not necessarily linked.…”
Section: Discussionmentioning
confidence: 99%